Analisis Kepuasan Pengguna Aplikasi PELNI Mobile Menggunakan Metode Technology Acceptance Model (TAM) dan End User Computing Satisfaction (EUCS) - Yutri Angriana Takke; Lion Ferdinand Marini; Lorna Yertas Baisa (Universitas Islam Raden Rahmat, Malang, 2024)
The presence of the PELNI application mobile makes it easier for people to make purchases online without having to go through the ticket purchase counter manually. This application is very important because it can be used as a source of evaluation to improve the quality of services provided by the application. The flow of this research includes the planning, data collection and data analysis stages. This research used 101 respondents and 15 statements. This research measures PELNI user satisfaction mobile. Based on the results of the analysis carried out using the TAM and EUCS methods, there were 2 accepted hypotheses, namely H1 and H3, and 3 rejected hypotheses, namely H2, H4, and H5. The results obtained through SEM-PLS analysis are classified as moderate with correlation values R-Square of 48.5% for the user satisfaction variable.